Budaya Partisipatif Fans K-Pop Dalam Aktivitas Noraebang Party (Studi Netnografi Pada Unggahan Konten Video #Noraebang Party Di Tiktok) - Firda Salsa Billah (Universitas Pakuan, 2026)
PARTICIPATORY CULTURE OF K-POP FANS IN NORAEBANG PARTY ACTIVITIES (A NETNOGRAPHIC STUDY OF #NORAEBANG PARTY VIDEO CONTENT UPLOADS ON TIKTOK) This study aims to describe the participatory culture of K-Pop fans in Noraebang Party activities on TikTok. Noraebang Party has developed as a fandom practice that functions not only as entertainment, but also as a medium for social interaction, identity formation, and popular cultural expression. This study uses a qualitative approach with a netnographic method by observing fans’ digital activities through video content uploaded with the hashtag #noraebangparty on TikTok. The research data were obtained through digital observation, documentation of video uploads, comment analysis, and short interviews with several users involved in the activity. The findings show that participatory culture in Noraebang Party is formed through fans’ active involvement in singing together, using K-Pop attributes, imitating idol styles, documenting activities, and sharing experiences through social media. These activities create a sense of togetherness among fandom members because fans do not merely act as audiences, but also participate in producing and distributing content. TikTok serves as a space that expands participation through comments, likes, reposts, and hashtag use. In addition, Noraebang Party demonstrates that K-Pop fandom has the ability to build an expressive, creative, and collaborative community. This activity also shows the exchange of meaning among fans through symbols, song lyrics, body movements, and visual attributes. Participation strengthens emotional closeness, belonging, and self-recognition as part of a fan community. Therefore, Noraebang Party can be understood as a form of participatory culture that combines entertainment, fan identity, and communication practices within a dynamic space of popular culture among young social media users.